PROTECTION OF TRADEMARK RIGHTS - Milica J. Cizmovic (Годишњак Правног факултета у Бањалуци)
Administrative trademark protection is reflected in imposing administrative measures against those persons who have violated a trademark right, but also in the supervision over the implementation of regulations directly referring to the trademark propriety. Customs play essential role in implementing trademark protection measures. Legal regulations of the European Union member states and TRIPS agreement regulate in detail the implementation of customs control with the aim to prevent infringement of a trademark. In order to ensure efficient work of customs offices against piracy and counterfeiting across national borders, it is necessary to ensure an efficient protection system, its implementation and a data base on registered trademarks available to customs officers. A special form of administrative control is carried out by means of inspection control. Inspection control ensures the control of enforcement of laws, bylaws and other regulations that are directly or indirectly related to trademark, with the aim to protect constitutionality and legality. Trademark Act contains provisions that regulate the issue of misdemeanour trademark protection as one of the forms of penalty sanctions in case of an infringement of a trademark is established. Although the issue of misdemeanour trademark protection in legislation of Bosnia and Herzegovina is characterized as a new area, and the number of court decisions is relatively small to go in favour of a relevant jurisprudence, in normative terms, Bosnia and Herzegovina is not lagging behind the neighbouring countries whose experience in the field of trademark protection has lasted longer and the number of their court decisions related to this field is higher.